Good Corporate Governance and Corporate Values with Profitability as a Moderating Variable in Manufacturing Companies Listed on The Indonesia Stock Exchange for the 2012-2021 Period - Yudi Partama Putra; Retno Triono; Hesti Setiorini; Desi Fitria; Ahmad Sumarlan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Abstract This study aims to examine the effect of managerial ownership, institutional ownership, independent board of commissioners, audit committee on firm value with profitability as a moderating variable in manufacturing companies listed on the IDX for the 2012 – 2021 period. The population in this study consisted of 193 manufacturing companies on the IDX for the 2012-2021 period which were selected based on certain criteria using purposive sampling. The research sample consisted of 17 companies, with an observation period of 10 years, so the research sample consisted of 275 samples. The data analysis used was panel data regression, and moderate regression analysis (MRA) was processed using the STATA 17 program. The partial test results prove that managerial ownership has no effect on firm value with a significance value of 0.960 > 0.05, institutional ownership has no effect on firm value with a significance value of 0.718 > 0.05, independent commissioners have an effect on firm value with a significance value of 0.000 <0.05. and the audit committee has no effect on firm value with a significance value of 0.372 > 0.05. Profitability can moderate the relationship between managerial ownership and firm value with a significance value of 0.017 <0.05. Profitability can moderate the relationship between institutional ownership and firm value with a significance value of 0.016 <0.05. Profitability can moderate the relationship between the independent board of commissioners and firm value with a significance value of 0.000<0.05. Profitability cannot moderate the relationship between the audit committee and firm value with a significance value of 0.057 > 0.05. The results of testing the coefficient of determination (Adjusted R-square) shows that the percentage of the independent variable on the dependent variable is 17.43% or it can be interpreted that the independent variable used in the model is able to explain 17.43% of the dependent variable while the rest is influenced by variables outside models.